2011
DOI: 10.4025/actascibiolsci.v33i2.6252
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos tóxicos de surfactantes fitossanitários para o peixe mato grosso (Hyphessobrycon eques)

Abstract: Os surfactantes são moléculas anfipáticas que reduzem a tensão superficial da água e fazem parte dos componentes inertes das formulações de produtos fitossanitários. Assim, os objetivos deste trabalho foram: estimar a concentração letal (CL(I)(50;96h)); classificar e avaliar a qualidade da água durante os testes de toxicidade aguda dos surfactantes: Agral ® , Aterbane ® BR, Ag-Bem ® , Energic ® , Fixade ® e Gotafix ® para o peixe mato grosso (Hyphessobrycon eques); e os sinais de intoxicação nos animais. Para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Other research based on the measurements of Cytochrome P4501A (CYP1A) induction in trouts showed that the exposition to surfactant-based dispersants (Corexit 9500) caused increase of the effects of crude oil hydrocarbons (Ramachandran et al, 2004). Recently, the ecotoxicological evaluation of commercial surfactants to fish jewel tetra (Hyphessobrycon eques) provided LC 50 values ranging from 2.34 to 34.95 mg/L after 96 h exposition (Carraschi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other research based on the measurements of Cytochrome P4501A (CYP1A) induction in trouts showed that the exposition to surfactant-based dispersants (Corexit 9500) caused increase of the effects of crude oil hydrocarbons (Ramachandran et al, 2004). Recently, the ecotoxicological evaluation of commercial surfactants to fish jewel tetra (Hyphessobrycon eques) provided LC 50 values ranging from 2.34 to 34.95 mg/L after 96 h exposition (Carraschi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos demonstraram efeitos tóxicos do formol em peixes, como agressão do epitélio branquial (Martins 2004), também há relatos que a toxicidade aumenta com a elevação da temperatura da água (Carraschi et al 2011) sendo esta afirmação muito importante para a realização de tratamentos em peixes tropicais. Para o sulfato de cobre é reportado que o mesmo é tóxico em água com baixa dureza e seu uso prolongado pode deixar os peixes debilitados (Bassleer 2011) além de que no ambiente natural já ocorrem problemas relacionados com o aumento da sua concentração nos corpos de água ocasionando efeitos tóxicos nos organismos aquáticos (Mazon et al 2002).…”
Section: Introductionunclassified
“…Regarding water quality parameters under experimental conditions or during production, there are reports of temperatures ranging from 20 °C (Santos et al, 2017) to 28.5 °C (Park et al, 2014), slightly acidic or even neutral pH (Carvalho & Del-Claro, 2004;Park et al, 2014;Silva et al, 2014;Berchielli-Morais et al, 2015;Silva et al, 2015;Marcon et al, 2016;Silva et al, 2016;Santos et al, 2017;Mansano et al, 2018;Miraldo & Pecora, 2017;Çelik & Cirik, 2019), and dissolved oxygen above 5.0 mg L -1 (Wang et al, 2006;Sotero-Santos et al, 2007;Pan et al, 2010;Carraschi et al, 2011;Pan et al, 2011;Aguinaga et al, 2014;Park et al, 2014;Silva et al, 2014;Berchielli-Morais et al, 2015;Silva et al, 2015;Marcon et al, 2016;Santos et al, 2017;Miraldo & Pecora, 2017). It should be noted that the conditions maintained in the experiments or in the cultivation of the species are similar to those observed in natural environments.…”
Section: Conditions Related To Water Quality Parameters For H Equesmentioning
confidence: 99%